Analisis Gaya Bahasa dalam Puisi Modern “Jalan Baru” karya Willy Fahmy Agiska - Gatri Andriani; Alber (Prakata: Jurnal Bahasa dan Sastra Indonesia Serta Pembelajaran, 2026)
This study aims to describe the types of figurative language used in the modern poem “Jalan Baru” by Willy Fahmy Agiska and to explain their meanings and functions in constructing the poem's message. This research employed a descriptive qualitative method with a stylistic approach. The data source was the poem “Jalan Baru”, which was analyzed through reading and note-taking techniques. The data consisted of words, phrases, lines, and stanzas containing figurative language elements, which were then classified and interpreted based on their types and functions. The results showed five types of figurative language: metaphor, personification, repetition, symbolism, and irony. Metaphor and symbolism were the most dominant forms, representing life changes, hope, human relationships, and reflections on life. Meanwhile, personification, repetition, and irony strengthened expression, emphasized meaning, and conveyed social criticism. Therefore, figurative language plays an important role in creating aesthetic value and deepening the meaning conveyed by the poet.